Lung Ultrasound Diagnostic Accuracy in Neonatal Pneumothorax - Luigi Cattarossi; Roberto Copetti; Giacomo Brusa; Stefano Pintaldi (Canadian Respiratory Journal)
Background. Pneumothorax (PTX) still remains a common cause of morbidity in critically ill and ventilated neonates. At the present time, lung ultrasound (LUS) is not included in the diagnostic work-up of PTX in newborns despite of excellent evidence of reliability in adults. The aim of this study was to compare LUS, chest X-ray (CXR), and chest transillumination (CTR) for PTX diagnosis in a group of neonates in which the presence of air in the pleural space was confirmed. Methods. In a 36-month period, 49 neonates with respiratory distress were enrolled in the study. Twenty-three had PTX requiring aspiration or chest drainage (birth weight 2120 ± 1640 grams; gestational age = 36 ± 5 weeks), and 26 were suffering from respiratory distress without PTX (birth weight 2120 ± 1640 grams; gestational age = 34 ± 5 weeks). Both groups had done LUS, CTR, and CXR. Results. LUS was consistent with PTX in all 23 patients requiring chest aspiration. In this group, CXR did not detect PTX in one patient while CTR did not detect it in 3 patients. Sensitivity and specificity in diagnosing PTX were therefore 1 for LUS, 0.96 and 1 for CXR, and 0.87 and 0.96 for CTR. Conclusions. Our results confirm that also in newborns LUS is at least as accurate as CXR in the diagnosis of PTX while CTR has a lower accuracy.